Congenital Diaphragmatic Hernia Presenting in a 7-Day-Old Infant. (4th January 2017) - Rouse, Christopher; Schmidt, Luke; Brock, Lee; Fagiana, Angela
Abstract : A 7-day-old male infant presented to the emergency room after respiratory distress was noted at an outpatient well child check. On exam, he was observed to have tachypnea, increased work of breathing, and decreased breath sounds on the left side of the chest. On chest X-ray, he was found to have a left-sided congenital diaphragmatic hernia. The infant was transported to a tertiary care facility where the defect was repaired without complication. Interestingly, the mother had a history of a normal antenatal ultrasound, completed at 19 + 2 weeks of gestational age. This case report summarizes the challenges of diagnosing late-presenting congenital diaphragmatic hernia, associated malformations, possible etiologies, and prognosis.